2016
DOI: 10.1002/lary.26105
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of small vestibular schwannoma on community ambulation, postural, and ocular control

Abstract: 4 Laryngoscope, 127:1147-1152, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
(120 reference statements)
0
1
1
Order By: Relevance
“…Our results showed that patients with vestibular schwannoma and Ménière's both have a reduced (6%) odds of falls compared with those with no vestibular disorders; others have reported a similar, counterintuitive relationship (55). Our result disagrees with previous literature reporting an elevated fall risk in patients with vestibular schwannoma (10%) compared with controls (56). Previous research has also demonstrated that patients with diagnosed Ménière's experience significantly greater hazard of falls (23%, using time-to-event analysis) than patients without Ménière's (57).…”
Section: Discussioncontrasting
confidence: 99%
“…Our results showed that patients with vestibular schwannoma and Ménière's both have a reduced (6%) odds of falls compared with those with no vestibular disorders; others have reported a similar, counterintuitive relationship (55). Our result disagrees with previous literature reporting an elevated fall risk in patients with vestibular schwannoma (10%) compared with controls (56). Previous research has also demonstrated that patients with diagnosed Ménière's experience significantly greater hazard of falls (23%, using time-to-event analysis) than patients without Ménière's (57).…”
Section: Discussioncontrasting
confidence: 99%
“…Unlike prior findings, gait speed during community ambulation appeared preserved, with both groups completing the community ambulation routes in a similar amount of time. 8,16 Ideally, following resection of a vestibular schwannoma, individuals will independently engage in head and body movements that provoke gaze and postural instability. Exposing the brain to such error signals appears to promote neural adaptation that restores gaze and postural stability function toward premorbid levels.…”
Section: Discussionmentioning
confidence: 99%